Una ripetizione straniante: L’idea fissa in un racconto di I.U. Tarchetti - Murru, Claudia (Incontri. Rivista europea di studi italiani, 2021)
Repetition and estrangementThe fixed idea in a tale of I. U. TarchettiThe article aims to investigate the process of estrangement through the tale La lettera U, by Iginio Ugo Tarchetti. By adopting the point of view of a madman, Tarchetti stages an estrangement that affects the entire discourse of the character. The fixed idea, a symptom of monomania (the psychiatric definition of this type of delirium at the time) gives rise to a narrative device with a strong alienating potential, able to highlight the differences between the notion of Šklovskij's ostranenie and estrangement as presented in fantastic literature.